IMPLEMENTASI TEKNOLOGI BLOCKCHAIN DAN SMARTCONTRACT STUDI KASUS PADA PENGELOLAAN SISTEM INFORMASI PRESTASI MAHASISWA DI UNIVERSITAS SEMARANG - basworo ardi pramono; Soiful Hadi; astrid novita putri (Lambung Mangkurat University, 2023)
Student achievement is an important point that is taken into account in determining a university accreditation. Free College Curriculum requires students to be creative in participating in activities and achievements outside of lectures. In this case, it becomes a complex factor and condition in considering and determining student achievement scholarships in the national and international scope. In this case, a blockchain technology is needed that can support managing student achievement data and verifying it from university management, so that it can increase student productivity in developing their achievements. As well as the data stored is Private Data which is very necessary for guaranteed and protected security which is not easy to hack and can track information easily and can only be done by the parties involved. So that information can be shared transparently. This research uses the RAD (Rapid Application Development) Model System Development Method, the Blockchain Algorithm Problem Solving Method and the Open Source Software used by Solidity. It is hoped that this research can increase trust and benefit both parties. Semarang university transparently